CLINIC OPERATIONAL EFFICIENCY THROUGH OPTIMIZING THE DISTRIBUTION OF NURSING STAFF - Barlian, Noer Aisyah; Faqih, Muhammad (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
An inpatient primary clinic is a healthcare unit characterized by fewer facilities and amenities compared to a hospital. Consequently, the distribution and allocation of health workers, particularly nurses, for operational processes differ significantly from that in hospitals. This study aims to determine the optimal number of nursing personnel required for efficient operation of an inpatient primary clinic through the application of linear programming techniques. The research methodology involves secondary data analysis, utilizing administrative information from inpatient private clinics in Lumajang Regency, East Java. The findings reveal that the linear programming model implemented is effective in optimizing nurse distribution. Specifically, the results indicate that a minimum of eight nurses is necessary to ensure efficient operation and cost-effectiveness of the inpatient clinic. This efficient distribution model can potentially lead to significant operational cost savings, thereby enhancing the overall performance and sustainability of inpatient primary clinics in similar settings.